Infection with hypervirulent Mycobacterium tuberculosis triggers emergency myelopoiesis but not trained immunity - Maceiras, Ana Raquel; Silvério, Diogo; Gonçalves, Rute; Cardoso, Marcos S.; Saraiva, Margarida (Frontiers in Immunology, 2023)
Introduction During infection, bone marrow (BM) hematopoiesis is reprogrammed toward myeloid cell production, a mechanism named emergency myelopoiesis. In addition to replenishing myeloid cells, emergency myelopoiesis has been linked to trained immunity, a process that allows enhanced innate immune responses to secondary challenges. Although hematopoietic alterations during tuberculosis (TB) have been described and Mycobacterium tuberculosis may colonize the BM, studies using the mouse model of infection and the laboratory reference strain M. tuberculosis H37Rv have demonstrated limited emergency myelopoiesis and trained immunity. Methods To further address this issue, we aerosol- infected C57BL/6 mice with high doses of the hypervirulent M. tuberculosis isolate HN878 and monitored alterations to the BM. This experimental model better resembles the human blood immune signature of TB. Results and discussion We found increased frequencies of lineage-Sca-1+cKit+ (LSK) cells and the granulocyte/macrophage progenitor (GMP) population. At the mature cell level, we observed an increase of monocytes and neutrophils in the blood and lung, likely reflecting the increased BM myeloid output. Monocytes or monocyte-derived macrophages recovered from the BM of M. tuberculosis HN878-infected mice did not show signs of trained immunity, suggesting an uncoupling of emergency myelopoiesis and trained immunity in the BM. Surprisingly, M. tuberculosis HN878-induced emergency myelopoiesis was not fully dependent on IFNγ, as mice lacking this cytokine and infected under the same conditions as wild-type mice still presented BM alterations. These data expand our understanding of the immune response to M. tuberculosis and raise awareness of pathogen strain-imposed differences to host responses.